2004
DOI: 10.1103/physrevlett.93.190501
|View full text |Cite
|
Sign up to set email alerts
|

Bound Entanglement Provides Convertibility of Pure Entangled States

Abstract: I show that two distant parties can transform pure entangled states to arbitrary pure states by stochastic local operations and classical communication (SLOCC) at the single copy level, if they share bound entangled states. This is the effect of bound entanglement since this entanglement processing is impossible by SLOCC alone. Similar effect of bound entanglement occurs in three qubits where two incomparable entangled states of GHZ and W can be inter-converted. In general multipartite settings composed by N d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
51
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 24 publications
2
51
1
Order By: Relevance
“…This is accomplished by proving a new entanglement activation result, which generalizes previous findings 14 and points toward an activation process involving two undistillable states which would, in particular, imply the existence of NPPT states. Entanglement activation [11][12][13][14][15][16][17][18][19][20] is the process in which an entangled state, which by itself would be useless for a given task, e.g., teleportation, can be activated and used as an a resource when processed together with a second state. In the first example of such a phenomenon, 15 it was shown that a certain PPT bound entangled state could be employed in order to increase the fidelity of teleportation of a second state.…”
Section: Introductionmentioning
confidence: 99%
“…This is accomplished by proving a new entanglement activation result, which generalizes previous findings 14 and points toward an activation process involving two undistillable states which would, in particular, imply the existence of NPPT states. Entanglement activation [11][12][13][14][15][16][17][18][19][20] is the process in which an entangled state, which by itself would be useless for a given task, e.g., teleportation, can be activated and used as an a resource when processed together with a second state. In the first example of such a phenomenon, 15 it was shown that a certain PPT bound entangled state could be employed in order to increase the fidelity of teleportation of a second state.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of bound entanglement [6], i.e., nonseparable states that possess a positive partial transpose and are useless to distill pure maximally entangled states by LOCC [7,8], suggest that there are other natural restricted classes of operations. One might add bound entangled states as a free resource to LOCC operations to achieve tasks that are impossible under LOCC alone [9][10][11]. Encompassing both classes is the mathematically more natural and convenient class of positive partial transpose preserving operations (PPT-operations) [12] which have the property that they map the set of positive partial transpose states into itself just as LOCC operations map the set of separable states into itself.…”
mentioning
confidence: 99%
“…Here, a map Λ is called PPT-preserving operations [17] when both Λ and Γ•Λ•Γ is a completely positive (CP) map with Γ being a map of the partial transpose [18]. On the other hand, the manipulation of mixed-state entanglement still suffers some restriction even under PPT-preserving operations in single-copy settings [15,16]. This implies that there certainly exists strong monotonicity independent on the Schmidt number in mixed-state entanglement manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the conversion between bipartite pure states, the Schmidt number is a unique strong monotone (the conversion is impossible when the Schmidt rank of the target state is larger than that of the initial state, but otherwise the conversion is possible with nonzero probability [13,14]). Positive partial transpose preserving (PPT-preserving) operations can overcome the monotonicity of the Schmidt number, and therefore all pure entangled states become convertible under PPT-preserving operations [15,16]. Here, a map Λ is called PPT-preserving operations [17] when both Λ and Γ•Λ•Γ is a completely positive (CP) map with Γ being a map of the partial transpose [18].…”
Section: Introductionmentioning
confidence: 99%